All‐Optical Signal Processing: Few‐Layer Topological Insulator for All‐Optical Signal Processing Using the Nonlinear Kerr Effect (Advanced Optical Materials 12/2015). Issue 12 (December 2015) - Chen, Shuqing; Miao, Lili; Chen, Xing; Chen, Yu; Zhao, Chujun; Datta, Subhadeep; Li, Ying; Bao, Qiaoliang; Zhang, Han; Liu, Yong; Wen, Shuangchun; Fan, Dianyuan
Abstract : On page 1769, Y. Li, H. Zhang, and co‐workers investigate the nonlinear optical properties of a topological insulator (TI, Bi2 Te3 ) and demostrate a novel all‐optical processing device by combing TIs and microfibers. The strong light‐matter interaction can be achieved through the interaction of TIs with the evanescent field of propagating light. The unique nonlinear Kerr effect ensures this TI‐based prototype device is realized with optical Kerr switching, and four‐wave mixing‐based wavelength conversion in the telecommunications band.